Prevalence of single and multiple reproductive disorders in Jersey crossbred cows of sub-tropical North-Western Himalayas - PANKAJ SOOD; ANKIT AHUJA (Indian Journal of Animal Sciences, 2023)
A total of 1612 cows during 118 rural infertility camps (October 2013 to February 2021) in Himachal Pradesh were examined for prevalence of single and multiple reproductive disorders. Subsequently, prevalence of reproductive disorder was analysed from a perspective of age (Group 1: ≤2.5 years; Group 2: 2.5-7 years; Group 3: ≥7 years) and season (summer, monsoon, post-monsoon and winter). In descending order, true anestrus, endometritis, infantile genitalia, repeat breeding and silent estrus were most prevalent single disorders. However, prolonged estrus with endometritis (62.3%) and metestral bleeding with repeat breeding (29.8%), respectively were concomitantly present as multiple disorders (in the same set of cows). Group 2 cows were highly susceptible for the presence of single and multiple disorders; whereas the disorders were most prevalent during pre-winter-winter and minimum during summer season.